2017
DOI: 10.2169/internalmedicine.56.7620
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Actinomycosis Mimicking Pulmonary Aspergilloma and a Brief Review of the Literature

Abstract: Pulmonary actinomycosis is a rare pulmonary infection that often exhibits unspecific symptoms and radiological findings. We herein report a case of pulmonary actinomycosis that mimicked pulmonary aspergilloma in an immunocompetent patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
(22 reference statements)
0
20
0
3
Order By: Relevance
“…The radiologic findings of pulmonary actinomycosis can resemble a broad spectrum of lung pathologies from benign infection to metastatic tumor, which make the diagnosis of this disease difficult, even for experienced physicians (13). In fact, our case showed that chest CT scan revealed a patchy nodular shadow with cavitation in the left upper lobe and surrounding ground glass opacities.…”
Section: Discussionmentioning
confidence: 76%
“…The radiologic findings of pulmonary actinomycosis can resemble a broad spectrum of lung pathologies from benign infection to metastatic tumor, which make the diagnosis of this disease difficult, even for experienced physicians (13). In fact, our case showed that chest CT scan revealed a patchy nodular shadow with cavitation in the left upper lobe and surrounding ground glass opacities.…”
Section: Discussionmentioning
confidence: 76%
“…The management of pulmonary actinomycosis is based on the use of prolonged infusions of beta-lactam antibiotics, although surgical management may be required in some cases [ 27 ]. Even though therapy should be individualized, the standard management is high doses of intravenous penicillin for 2–6 weeks followed by oral therapy with penicillin V or amoxicillin for 6–12 months [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Изменения в легких, выявляемые при КТ-исследовании и имитирующие аспергиллому, могут наблюдаться при других редких инфекционных заболеваниях, таких как кокцидиоидомикоз, нокардиоз, актиномикоз, эхинококковые кисты легких [41,45].…”
Section: простая одиночная аспергилломаunclassified
“…Современные публикации подтверждают, что позитронно-эмиссионная томография в сочетании с КТ с радиофармпрепаратом в диагностике хронического нодулярного аспергиллеза не является специфичным исследованием, так как аспергиллезные узлы могут активно накапливать 18 F-фтордезоксиглюкозу, что может создавать ложное представление о наличии опухоли [45,[57][58][59].…”
Section: нодулярный аспергиллезunclassified